Community-based study on the knowledge, awareness, and practices of females towards breast cancer in Buraimi, Oman - Chattu, Vijay Kumar; Kumary, Soosanna; Bhagavathula, Akshaya Srikanth (South Asian Journal of Cancer, 2018)
Background: In Oman, a higher proportion of patients presented with breast cancer are relatively young age and with an advanced stage. This could be due to lack of awareness and knowledge about breast cancer among young women. Aim: To assess the breast cancer knowledge, awareness and factors associated with the practice of breast self-examination (BSE) among females in Buraimi, Oman. Methods: A cross-sectional survey was conducted among females attending the two days health exhibition event at a polyclinc, in Al-Buraimi, governorate. A pretested questionnaire to assess their knowledge, awareness and practices concerned to breast cancer was used. The collected data was categorized, analyzed using descriptive statistics and logistic regression model. All the statistical analysis was performed using SPSS 21.0 version. Results: Out of the total of one hundred and eighty nine (189) participants, 80% had information of breast cancer. Participants had better knowledge of symptoms but less knowledge about risk factors. When probed about BSE, only 43% performed it and only 21% of them do it monthly on regular basis. The main reasons for regular monthly BSE is mainly because of fear of breast cancer (9%), doctor's advice (6%) and awareness through media (5%). Conclusion: Our study participants showed insufficient knowledge in some areas related to sign and symptoms and risk factors of breast cancer and identified a negative influence of low knowledge on the practice of BSE. Thus, educational interventions need to be emphasized to provide comprehensive information of breast cancer.
Keywords: Awareness; breast cancer; breast self-examination; community-based; knowledge; Middle East; Oman; screening; young females